Izzivi učinkovite rabe energije – se jih družbe in institucije zavedajo? (University of Maribor Press, 2017)
Challenges to energy efficiency - are companies and institutions aware of them? Monograph examines the issues related to the efficient use of energy and use of renewable sources in Slovenia and the world. In order to encourage business consumers towards efficient use of energy monograph provides analysis of current situation and offers several recommendations. The first part includes the analysis of present situation, a brief historic overview and future directions for Slovenia. Added is an introduction of concepts and a review of scientific literature about business consumers’ attitudes towards EEU and RES. Second part shows practical examples of Slovenian companies’ efforts to comply with the goals of EU and Slovenian energy policies. Final part of the monograph reveals the results of a longitudinal study of managers’ attitudes towards EEU and RES in Slovenia. The study shows that electricity consumption by business consumers in Slovenia is on the rise – also at the expense of reducing fossil fuel consumption. Consequently companies are more frequently looking for solutions for responsible use of electricity, which also include plans on investments in self-sufficiency systems. Sun energy appears to be the most appealing source of energy, which is also emphasized in preceding chapters.